A bibliometric analysis of PIN1 and cell death - Zhang, Jia-Heng; Ni, Shi-Yu; Tan, Ya-Ting; Luo, Jia; Wang, Shu-Chao (Frontiers in Cell and Developmental Biology, 2022)
Background: As a proline isomerase, Pin1 is important in the regulation of signaling pathways. Regulated cell death plays a key role in numerous diseases. An in-depth understanding of how Pin1 participates in the process of cell death and thus affects the occurrence and development of diseases will help to discover new disease mechanisms and therapeutic methods. The purpose of our study is to discover the research trends and hotspots of Pin1 and cell death through bibliometric analysis, and to provide views for understanding the future development of basic research and treatment of diseases. Methods: Documents were extracted from the Web of Science Core Collection on May 7, 2022. We selected articles and reviews published in English from 2000 to 2021 to perform visual analysis and statistical analysis of countries, institutions, authors, references and keywords by VOSviewer 1.6.18 and CiteSpace 5.8. Results: A total of 395 articles and reviews were selected. Since 2001, the number of articles on Pin1 and cell death has increased year by year. Publications come from 43 countries, with the US with the most publications and citations. We identified 510 authors, with Giannino Del Sal with the most articles and Paola Zacchi with the most co-citations. Journal of Biological Chemistry is the most researched journal, and Nature and its sub-journals are the most cited journals. Apoptosis, phosphorylation, and breast cancer were the three most common keywords. Conclusion: The number of documents showed an increasing trend from 2001 to 2014. The stagnant growth after 2014 may be related to the absence of new research hotspots. Cooperative links between core institutions need to be strengthened, and the institution with the highest citation outbreak in recent years is Fujian Medical University in China. The field of Pin1 and cell death needs more research to discover new research hotspots. Before breakthroughs in molecular mechanism or signaling pathway research, future research will focus more on the treatment of diseases represented by Pin1 inhibitors.